Local Small Ruminant Grazing in the Monti Foy Area (Italy): The Relationship Between Grassland Biodiversity Maintenance and Added-Value Dairy Products - Claps, Salvatore; Mecca, Marisabel; Di Trana, Adriana; Sepe, Lucia (Frontiers in Veterinary Science, 2020)
The literature indicates that grazing small ruminants, when adequately managed, contributes to grassland biodiversity maintenance. On the other hand, milk and cheese from grazing animals show higher nutritional and aromatic quality than those from stall-fed animals. The relationship between the two issues has rarely been addressed. This article provides information for a discussion of this relationship. First, two case studies are reported. Local breeds of small ruminants fed by grazing on pastures within the Special Area of Conservation “Monti Foy” in the Northwestern Basilicata region (Italy), with a stocking rate of 4.0 LU ha−1 year−1, showed the best effectiveness for the maintenance of grassland botanical biodiversity. Milk and cheese from pasture-fed goats showed higher contents of beneficial fatty acids, phenols, and vitamins A and E; higher degree of antioxidant protection; and richer volatile compound profiles, in particular for terpenes content. Finally, some recommendations for the management of grazing systems in similar mountain areas are offered, including a viable approach for land managers to preserve the grassland biodiversity of pastures and provide high-quality products that are valuable both for their nutritional quality and for their contribution to the economic sustainability of mountain communities.